2021
DOI: 10.1371/journal.pone.0250801
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coronary risk factors in contemporary practice among patients undergoing their first percutaneous coronary intervention: Implications for primary prevention

Abstract: Background Cigarette smoking, hypertension, dyslipidemia, diabetes, and obesity are conventional risk factors (RFs) for coronary artery disease (CAD). Population trends for these RFs have varied in recent decades. Consequently, the risk factor profile for patients presenting with a new diagnosis of CAD in contemporary practice remains unknown. Objectives To examine the prevalence of RFs and their temporal trends among patients without a history of myocardial infarction or revascularization who underwent thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“… 9 (2008) Retrospective study To examine whether sex-based differences in mortality after PCI have changed in the past 25 years 1979–1995 N = 7904 W: 2203 (27.9%) Mean age, y: 67.3 ± 11.1 M: 5701 (72.1%) Mean age, y: 62.4 ± 11.2 1996–2004 N = 10,981 W: 3365 (30.6%) Mean age, y: 69.4 ± 12.0 M: 7616 (69.4%) Mean age, y: 64.7 ± 11.8 Ethnicity: NA Origin of the study: US 1979–1995 DB: W: 23%, M: 15% HTN: W: 60%, M: 44% Smoking: W: 19%, M: 23% HTN > DB 1996–2004 DB: W: 28%, M: 22% HTN: W: 73%, M: 60% Smoking: W:18%, M: 20% DB: P = 0.007 HTN: P = 0.46 Smoking: P = 0.34 Gurm et al. 10 (2021) Prospective study Examination of the prevalence of RFs N = 108,501 W: 38,930 (35.9%) Age, y: ≤ 45: 5.8% 46–55: 14.98% 56–65: 25.8% 66–75: 27.37% ≥ 75: 26.47% (+ W aged ≥ 65 y) M: 69,571 (64.1%) Ethnicity: White: W (83.3%), M (87.3%) Black: W (14.1%), M (9.5%) Asian: W (0.9%), M (1.2%) American Indian or Alaskan native: W (0.3%), M (0.3%) Origin of the study: US Age ≤ 45 y: Smoking: W: 66%, M: 62.1% HTN: W: 62.3%, M: 56.4% OB: W: 62.3%, M: 56.9%, DLP : W: 47.2%, M: 50.2% DB: W: 35.8%, M: 20.5%. No P -value Age 46–55 y: Smoking: W: 61.1%, M: 52.4% HTN: W: 70%, M: 63.8% OB: W: 55.5%, M: 50.5% DLP: W: 61.1%, M: 59.2% DB: W: 33.5%, M: 23.7%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 (2008) Retrospective study To examine whether sex-based differences in mortality after PCI have changed in the past 25 years 1979–1995 N = 7904 W: 2203 (27.9%) Mean age, y: 67.3 ± 11.1 M: 5701 (72.1%) Mean age, y: 62.4 ± 11.2 1996–2004 N = 10,981 W: 3365 (30.6%) Mean age, y: 69.4 ± 12.0 M: 7616 (69.4%) Mean age, y: 64.7 ± 11.8 Ethnicity: NA Origin of the study: US 1979–1995 DB: W: 23%, M: 15% HTN: W: 60%, M: 44% Smoking: W: 19%, M: 23% HTN > DB 1996–2004 DB: W: 28%, M: 22% HTN: W: 73%, M: 60% Smoking: W:18%, M: 20% DB: P = 0.007 HTN: P = 0.46 Smoking: P = 0.34 Gurm et al. 10 (2021) Prospective study Examination of the prevalence of RFs N = 108,501 W: 38,930 (35.9%) Age, y: ≤ 45: 5.8% 46–55: 14.98% 56–65: 25.8% 66–75: 27.37% ≥ 75: 26.47% (+ W aged ≥ 65 y) M: 69,571 (64.1%) Ethnicity: White: W (83.3%), M (87.3%) Black: W (14.1%), M (9.5%) Asian: W (0.9%), M (1.2%) American Indian or Alaskan native: W (0.3%), M (0.3%) Origin of the study: US Age ≤ 45 y: Smoking: W: 66%, M: 62.1% HTN: W: 62.3%, M: 56.4% OB: W: 62.3%, M: 56.9%, DLP : W: 47.2%, M: 50.2% DB: W: 35.8%, M: 20.5%. No P -value Age 46–55 y: Smoking: W: 61.1%, M: 52.4% HTN: W: 70%, M: 63.8% OB: W: 55.5%, M: 50.5% DLP: W: 61.1%, M: 59.2% DB: W: 33.5%, M: 23.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Only 7 of 18 studies reported the ethnicity of patients. 6 , 10 , 15 , 18 , 19 , 20 , 24 The majority of participants in studies included in the present meta-analysis were Caucasian (roughly 70% of the cohorts), and around 15% of patients were African American or Afro-Caribbean. A small minority of participants were Hispanic or Asian.…”
Section: Resultsmentioning
confidence: 99%
“…Both registries include a similar proportion of non‐White patients, making it less likely that racial/ethnic differences in cardiometabolic risk factors could account for the observed disparity. The increased proportion of diabetic patients in Michigan undergoing PCI parallels the rise in diabetes in Michigan and more broadly the US and highlights the cardiovascular challenges of this silent epidemic 15 …”
Section: Discussionmentioning
confidence: 99%
“…The increased proportion of diabetic patients in Michigan undergoing PCI parallels the rise in diabetes in Michigan and more broadly the US and highlights the cardiovascular challenges of this silent epidemic. 15 One of the most striking differences in PCI practice pattern between the two cohorts was the use of radial access for PCI. The uptake of radial access is known to be variable throughout the United States particularly in the setting of acute coronary syndrome 16 and the Michigan trend generally matched or outpaced contemporaneous national data in the United States during the study period, 17,18 though this consistently lagged behind the UK.…”
Section: Primary Pci For Stemimentioning
confidence: 99%
“…The main risk factors of ischemic heart disease in this registry were smoking tobacco 61.6%, hypertension 56%, dyslipidemia 48.4%, and diabetes mellitus 37%. Smoking was slightly higher than the Egyptian patients at 59.05%,[ 9 ] Oman at 20%,[ 7 ] and among men in Michigan, United States of America (USA), at 34.5%[ 10 ] followed by hypertension at 56% which is lower than hypertension in Egypt and almost similar to that of Oman but less than hypertension among men in the USA (71.9%). Dyslipidemia was higher than in Egypt but less than in Oman and the USA.…”
Section: Discussionmentioning
confidence: 99%